A New Green Approach of CFIA Technique for Direct Assay with a High Throughput of Sulfamethoxazole Drugs Using Condensation Reaction with NQS Agent (Baghdad Science Journal, 2024)
A new design of manifold flow injection (FI) coupling with a merging zone technique was studied for sulfamethoxazole determination spectrophotometrically. The semiautomated FI method has many advantages such as being fast, simple, highly accurate, economical with high throughput . The suggested method based on the production of the orange- colored compound of SMZ with (NQS)1,2-Naphthoquinone-4-Sulphonic acid Sodium salt in alkaline media NaOH at λmax 496nm.The linearity range of sulfamethoxazole was  3-100  μg. mL-1, with (LOD) was 0.593 μg. mL-1 and the RSD% is about 1.25 and the recovery is 100.73%. All various physical and chemical parameters that have an effect on the stability and development of the colored product were accurately studied and the designed systems have been completely implemented successfully for sulfamethoxazole quantity estimation in pharmaceutical formulations and biological samples.